The Influence of Service Quality on Customer Loyalty Mediated by Customer Satisfaction - Karo Karo, Gilberte; Yuniarinto, Agung (Jurnal Manajemen Pemasaran dan Perilaku Konsumen, 2025)
Today's modern lifestyle requires a person to be able to manage their time as efficiently and effectively as possible in everyday life. These changes require life to become more practical and. Service quality is a series of services provided to consumers. From this service quality, customer satisfaction can be formed, and in the end, if customer satisfaction occurs repeatedly, customer loyalty is formed. The aim of this research is to determine the indirect effect of service quality on customer loyalty which is mediated by customer satisfaction at Inama Laundry. This research will take a minimum sample of 130 respondents and comply with the rule of thumb sample size criteria. Data were analyzed using SmartPls 4.0. The results of this research are that Customer Satisfaction has a positive and significant effect on Customer Loyalty, Service Quality has a positive and significant effect on Customer Loyalty through the mediation of customer satisfaction. The Customer Satisfaction variable in the relationship between Service Quality and Customer Loyalty in this study shows partial mediation.